SOLVING DIFFERENTIAL EQUATION USING SPIRAL DYNAMICS OPTIMIZATION ALGORITHM - RAMADHANINGRUM , ZUHAIRINA
Differential equations are one of the most widely used mathematical equations in many fields. The problem that often occur is not all differential equations can be solved or sought the solution exactly. So there are several ways to approximate the solution of the differential equation. One of them is approximate the solution of differential equations using Fourier series. Then, the coefficients of the Fourier series are determined by formulating the problem of differential equations into optimization problems. The spiral dynamics optimization algorithm which is one of the metaheuristic methods used to solve the optimization problem to determines the coefficient of the Fourier series. Thus, the approximate solution of differential equation is represented in the form of Fourier series with fairly small errors.